Transcranial Magnetic Stimulation Trains at 1 Hz Frequency of the Right Posterior Parietal Cortex Facilitate Recognition Memory - Mangano, Giuseppa Renata; Oliveri, Massimiliano; Smirni, Daniela; Tarantino, Vincenza; Turriziani, Patrizia (Frontiers in Human Neuroscience, 2021)
Neuroimaging, neuropsychological, and brain stimulation studies have led to contrasting findings regarding the potential roles of the lateral parietal lobe in episodic memory. Studies using brain stimulation methods reported in the literature do not offer unequivocal findings on the interactions with stimulation location (left vs. right hemisphere) or memory phase (encoding vs. retrieval). To address these issues, active and sham 1 Hz repetitive transcranial magnetic stimulation (rTMS) trains of 600 stimuli were applied over the right or left posterior parietal cortex (PPC) before the encoding or before the retrieval phase of a recognition memory task of non verbal stimuli in a group of 48 healthy subjects. Active rTMS over the right but not the left PPC significantly improved non verbal recognition memory performance without any significant modulation of speed of response when applied before the retrieval phase. In contrast, rTMS over the right or the left PPC before the encoding phase did not modulate memory performance. Our results support the hypothesis that the PPC plays a role in episodic memory retrieval that appears to be dependent on both the hemispheric lateralization and the memory phase (encoding vs. retrieval).